2010
DOI: 10.1371/journal.ppat.1001195
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Size-Dependent Neutralization Properties of HK20, a Human Monoclonal Antibody Binding to the Highly Conserved Heptad Repeat 1 of gp41

Abstract: The human monoclonal antibody (mAb) HK20 neutralizes a broad spectrum of primary HIV-1 isolates by targeting the highly conserved heptad repeat 1 (HR1) of gp41, which is transiently exposed during HIV-1 entry. Here we present the crystal structure of the HK20 Fab in complex with a gp41 mimetic 5-Helix at 2.3 Å resolution. HK20 employs its heavy chain CDR H2 and H3 loops to bind into a conserved hydrophobic HR1 pocket that is occupied by HR2 residues in the gp41 post fusion conformation. Compared to the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 61 publications
(95 reference statements)
2
84
0
Order By: Relevance
“…These aspects influence the potency and breadth of neutralization, which are higher for HK20 than for D5 and depend on somatically mutated residues. In addition, it was shown that in the case of HK20, the scFv is at least 15-fold more potent in neutralization than IgG, which is consistent with a limited accessibility to the target site (112). The gp41 footprints of HK20 and D5 and the global structural principles employed by the two antibodies are similar.…”
Section: Gp41 Immunogenicitymentioning
confidence: 75%
See 1 more Smart Citation
“…These aspects influence the potency and breadth of neutralization, which are higher for HK20 than for D5 and depend on somatically mutated residues. In addition, it was shown that in the case of HK20, the scFv is at least 15-fold more potent in neutralization than IgG, which is consistent with a limited accessibility to the target site (112). The gp41 footprints of HK20 and D5 and the global structural principles employed by the two antibodies are similar.…”
Section: Gp41 Immunogenicitymentioning
confidence: 75%
“…The gp41 footprints of HK20 and D5 and the global structural principles employed by the two antibodies are similar. Since HK20 targets HR1 instead of MPER or glycans in this region, it has the conceptual advantage over 4E10 and 2F5 of avoiding potential autoreactivity (112). HK20 presents an intermediate breadth of neutralization, preferentially to clades A and C, which did not correspond with the subtype of the infected patient, which was CRF02_AG as described in reference 1.…”
Section: Gp41 Immunogenicitymentioning
confidence: 99%
“…To estimate the fraction of antibodies specific for conserved GII.4 epitopes in the overall serum antibody response, 100 serum samples collected from healthy individuals were assayed for the ability to block binding of human MAbs NVB 61.3 and NVB 71.4 in a BOB assay (57,58). Both human MAbs recognize a broad panel of antigenically diverse, epidemiologically significant GII.4 NoV strain VLPs by EIA, but only NVB 71.4 blocks VLP-ligand interactions (47).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 4A shows a superposition of the covNHR3-ABC structure to the theoretical model of the gp41 ectodomain generated from the coordinates of the simian immunodeficiency virus gp41 ectodomain (1IF3) (21) and the crystallographic structure of the five-helix construct (2XRA) (7). The backbones of the two parallel NHR helices are wellsuperimposed, with an rmsd of 1.4 Å.…”
Section: Biophysical Characterization Of Second Generation Covnhr Promentioning
confidence: 99%
“…This exposed conformation was shown by the elicitation of Abs that block HIV fusion using immunogens exposing an NHR coiled coil (5). Also, two human mAbs (D5 and Hk20) recognize a highly conserved NHR hydrophobic pocket and neutralize diverse HIV-1 clinical isolates (6,7). Moreover, potent HIV-1-neutralizing CHR peptides, pioneered by T20, and small molecules bind to the trimeric NHR, interfering with formation of the NHR/CHR six-helix bundle (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%